Windows XP for Dummies Quick Reference 2nd Edition (Wiley Publishing, 2011)
Next to your keyboard and mouse, this could be your most important accessory. Just keep it next to your keyboard and your mouse and refer to it to capitalize on the terrific capabilities at your fingertips with Windows XP. Windows XP For Dummies Quick Reference Second Edition covers the latest updates to Windows XP, including enhanced security and changes to Internet Explorer. It starts with the basics for true beginners, goes through everyday stuff, and progresses to the Web, accessories, and the control panel. After a quick introduction to the desktop, My Documents, dialogue boxes, and other basic info, you’ll explore: - Customizing your desktop - Saving music with Windows Media Player - Browsing drives, folders and files - Dragging, dropping, cutting, and pasting - Playing music, videos and movies - Browsing with Internet Explorer - Sending and receiving e-mails - Using Windows Accessories